Perdagangan Aset Digital Game Online dalam Perspektif Fiqih Muamalah: Studi Kasus Peran Kyai Kampung - Lina Amelia; Ahmad Djalaluddin (STAI Al-Mas'udiyah, 2025)
This study aims to explore the dynamics of digital asset trading among rural youth and to analyze the phenomenon through the lens of Islamic economic jurisprudence (fiqh muamalah), especially from the perspective of local religious leaders known as kyai kampung. This research employed a qualitative case study method, using in-depth interviews, participatory observation, and documentation to collect data from kyai, teenage traders, and community figures. The findings reveal that various digital game assets such as game accounts, character skins, diamonds, and virtual chips are actively traded through social media platforms like WhatsApp and Facebook, with payments processed via digital wallets. The absence of formal contracts and regulatory oversight exposes these transactions to elements of gharar (uncertainty), maysir (gambling), and tadlis (fraud). While local kyai generally lack specific knowledge of digital asset jurisprudence, they demonstrate awareness of the moral and social impacts, especially concerning addiction and misuse. The study concludes that such practices can be permissible under Islamic law if they meet clear and lawful contractual standards. Strengthening digital fiqh muamalah literacy and building partnerships between local religious leaders and Islamic economic educators are essential to ensure ethical compliance in digital economic practices.